An Analysis of GAVI, the Global Fund and World Bank support for human resources for health in developing countries (2012)
Analyses the HRH-related activities of three agencies: Global Alliance for Vaccines and Immunisation (GAVI); the Global Fund for AIDSm Tuberculosis, and Malaria (the Global Fund); and the World Bank.
Keywords: HEALTH